Pengembangan Mekanisme Mutasi Masuk PNS Berbasis Manajemen Talenta ke Lingkungan Pemerintah Daerah Provinsi Jawa Barat - Aji Surya Utama; Ely Sufianti; Hendrikus Tribawanto Gedeona (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2023)
The Mutation of civil servants is an important step taken by the agency to get civil servants from outside the agency following the organization's needs to accelerate the achievement of organizational goals. The purpose of this study was to produce recommendations for developing a transfer mechanism for civil servants based on the talent management transfer mechanism for the West Java Provincial Government. The research method used is a qualitative research method with the type of descriptive research with data collection techniques through in-depth interviews, observation, and documentation to test the validity of the data using triangulation techniques and sources. The results of this study indicate that the implementation of the selection of mutations for entering civil servants to the Regional Government of West Java Province still has several problems. The problem because the regulations used are not relevant to the transfer mechanism for civil servants and are not following the implementation of talent management. The obstacles faced are the lack of human resources to update regulations, the absence of an application system, and technical competency instruments. An alternative solution to improving the mechanism for entering civil servants is the development of a talent management-based transfer mechanism for civil servants through the preparation of relevant regulations, preparation of transfer applications, preparation of technical competency instruments, as well as additional mechanisms such as selection of competency assessments, preparation of innovation papers and final interviews to provide optimal public services to the West Java Community.